Optic tectum morphogenesis: A step-by-step model based on the temporal-spatial organization of the cell proliferation. Significance of deterministic and stochastic components subsumed in the spatial organization - Rapacioli, Melina (2012)
Background: Cell proliferation plays an important morphogenetic role. This work analyzes the temporal-spatial organization of cell proliferation as an attempt to understand its contribution to the chick optic tectum (OT) morphogenesis. Results: A morphogenetic model based on space-dependent differences in cell proliferation is presented. Step1: a medial zone of high mitotic density (mZHMD) appears at the caudal zone. Step2: the mZHMD expands cephalically forming the dorsal curvature and then duplicates into two bilateral ZHMDs (bZHMD). Step3: the bZHMDs move toward the central region of each hemitectum. Step4: the planar expansion of both bZHMD and a relative decrement in the dorsal midline growth produces a dorsal medial groove separating the tectal hemispheres. Step5: a relative caudal displacement of the bZHMDs produces the OT caudal curvature. Numerical sequences derived from records of mitotic cells spatial coordinates, analyzed as stochastic point processes, show that they correspond to 1/f (β) processes. The spatial organization subsumes deterministic and stochastic components. Conclusions: The deterministic component describes the presence of a long-range influence that installs an asymmetric distribution of cell proliferation, i.e., an asymmetrically located ZHMD that print space-dependent differences onto the tectal corticogenesis. The stochastic component reveals short-range anti-correlations reflecting spatial clusterization and synchronization between neighboring cells. © 2012 Wiley Periodicals, Inc.